Software defined networks and network functions virtualization for critical and reliable communications in 5G environments - Filipe, João Miguel Barraca (2018)
The Fifth Generations of Mobile Networks (5G), driven by the aim to further connect today’s society, will have to make use of new emerging technologies such as Software Defined Networking (SDN) and Network Functions Virtulization (NFV) to cope with all the increasing traffic and services that are arising. Critical and Reliable services will make use of these technologies to create new mechanisms and/or to instantiate network functions that have very strict requirements in virtualized environments. The use of these Virtual Network Functions (VNFs) presents several advantages like fast re-instantiation in case of failure or scaling capabilities that are provided by nowadays Cloud infrastructures. In this thesis a study is made comparing the performance of Containers and lightweight Virtual Machines (Unikernels) for the instantiation of a network function in a virtualized environment with restricted resources. It is also implemented a mechanism to ensure the reliability of the VNF. Results show that Containers perform better in the use-case presented and the proposed reliability mechanisms ensure zero downtime for the VNF in case of failure.